2018
DOI: 10.1002/1873-3468.13025
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐ and heat‐induced protein unfolding in bacterial cells: crowding vs. sticking

Abstract: In-cell protein stability is increased by crowding, but can be reduced by destabilizing surface interactions. Will different denaturation techniques yield similar trends? Here, we apply pressure and thermal denaturation to green fluorescent protein/ReAsH-labeled yeast phosphoglycerate kinase (PGK) in Escherichia coli cells. Pressure denaturation is more two state-like in E. coli than in vitro, stabilizing the native state. Thermal denaturation destabilizes PGK in E. coli, unlike in mammalian cells. Results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Finally, we anticipate that the effect of hydrostatic pressure on protein compaction and folding is negligible under our conditions because the pressure necessary to unfold PGK-FRET is >600 bar. 52 Therefore, cytoskeletal drugs can produce two competing crowding effects inside cells: depolymerizing the cytoskeleton decreases crowder size and increases the fluidity of the cytoplasm, whereas reduced cell volume increases the extent of crowding.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Finally, we anticipate that the effect of hydrostatic pressure on protein compaction and folding is negligible under our conditions because the pressure necessary to unfold PGK-FRET is >600 bar. 52 Therefore, cytoskeletal drugs can produce two competing crowding effects inside cells: depolymerizing the cytoskeleton decreases crowder size and increases the fluidity of the cytoplasm, whereas reduced cell volume increases the extent of crowding.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Other recent work has shown that a eukaryotic probe protein introduced into E . coli will be less destabilized by pressure than temperature denaturation in E. coli , relative to in vitro pressure and temperature denaturation results [33]. Thus, destabilization of the protein by ‘sticking’ to the cytoplasmic matrix is mitigated by high pressure (better crowding), but enhanced by high temperature (stronger hydrophobic effect [34]).…”
Section: Folding Phase Diagrams Under Extreme Conditionsmentioning
confidence: 99%
“…In addition to their role in the spatial arrangement of the cellular milieu, quinary interactions modulate protein folding and stability . In‐cell studies showed that quinary interactions can have both stabilising and destabilising effects on globular proteins. The role of these opposite effects is still not clear but preliminary evidences suggests a dependence on protein sequence, function and location .…”
Section: Intracellular Spatial Organisation: the Emerging Role Of Quimentioning
confidence: 99%
“…These interactions, also known as nonsteric or soft interactions, are those that a protein can perform with its surroundings beyond the steric interactions that result from the excluded volume effect . They stabilise or destabilise globular proteins through charge–charge, polar, hydrogen bond and hydrophobic contacts with both the native and unfolded states (for more details see Appendix 1) . The magnitude of this modulation ranges on average from 0.1 to 1.1 kcal·mol −1 .…”
Section: Physicochemical Properties Of the Intracellular Environment mentioning
confidence: 99%
See 1 more Smart Citation